Students' satisfactions towards library service quality at a local higher learning institution - Nouremon-Dai, Fatimah (IIUM Press, 2011)
A brief study on student satisfaction towards library service quality in one of the local higher learning institutions. Using the SERVQUAL framework, the study tried to examine the service quality gap based on five factors namely tangibles, reliability, responsiveness, assurance and empathy. Further research was also suggested.